Australian Opilonini (Coleoptera: Cleridae: Clerinae) part I: A revised taxonomy for Australian Opilo Latreille including descriptions of new genera and species - Bartlett, Justin S.; Lambkin, Christine L. (Zootaxa, 2022)
The species- and genus-level taxonomy of Australian species assigned to Opilo Latreille is assessed and revised in the context of a morphological species concept. Australian species are deemed not congeneric with Opilo mollis (Linnaeus), the type species of Opilo Latreille. Species are grouped into genera by degree of difference observed in states of the tegmen, median lobe, antennal scape, basitarsi, hindwing, elytral striae and pronotal disc. Examination of 1,259 specimens resulted in recognition of 6 genera and 44 species, 36 of which are new to science. The following new genera are proposed: Ancyropilus gen. nov.; Culcipternulus gen. nov.; Infectostriatus gen. nov.; Monilonotum gen. nov.; Notopilo gen. nov.; Platynotum gen. nov.. Three infraspecific taxa described as ‘varieties’, viz, Opilo congruus var. abdominalis Schenkling, 1901, Notoxus congruus var. femoralis Westwood, 1849 and Opilo pascoei var. doddi Schenkling, 1906, are elevated to species status, with Opilo abdominalis (occupied by Opilo abdominalis Fairmaire, 1891) requiring a replacement name. The 44 species recognised in this revision are: Ancyropilus brigalowae sp. nov.; Ancyropilus emmotti sp. nov.; Ancyropilus exossuarius sp. nov.; Ancyropilus hornensis sp. nov.; Ancyropilus labris sp. nov.; Ancyropilus monteithi sp. nov.; Ancyropilus noonbahensis sp. nov.; Ancyropilus packsaddlensis sp. nov.; Ancyropilus simplex sp. nov.; Ancyropilus tricolor sp. nov.; Culcipternulus mareebensis sp. nov.; Infectostriatus absentis sp. nov.; Infectostriatus differens sp. nov.; Monilonotum bunyense sp. nov.; Monilonotum doddi (Schenkling, 1906) stat. rev., comb. nov. (transferred from Opilo); Monilonotum eburneocincta (Gorham, 1878) comb. nov. (transferred from Opilo); Monilonotum pascoei (Gorham, 1876) comb. nov. (transferred from Opilo); Monilonotum rufiventre (Gerstmeier, 1990) comb. nov. (transferred from Olesterus); Monilonotum sundholmi sp. nov.; Notopilo beswickensis sp. nov.; Notopilo brevistriatus sp. nov.; Notopilo calicis sp. nov.; Notopilo cambageicola sp. nov.; Notopilo confusus sp. nov.; Notopilo congruus (Newman) comb. nov. (transferred from Opilo); Notopilo elstoni sp. nov.; Notopilo eremosus sp. nov.; Notopilo gerstmeieri sp. nov.; Notopilo interfabulatus sp. nov.; Notopilo katherinensis sp. nov.; Notopilo lawnhillensis sp. nov.; Notopilo magnus sp. nov.; Notopilo obesus sp. nov.; Notopilo reduncus stat, rev., nom. nov. (replacement name for Opilo abdominalis Schenkling, 1901); Notopilo tanybasilaris sp. nov.; Notopilo tompricensis sp. nov.; Notopilo variipes (Chevrolat) comb. nov. (transferred from Opilo); Notopilo xanthoimprocerus sp. nov.; Notopilo xanthoprolatus sp. nov.; Platynotum bulli sp. nov.; Platynotum culgoense sp. nov.; Platynotum femorale (Westwood) stat. rev., comb. nov. (transferred from Opilo); Platynotum foveosetosa sp. nov.; Platynotum gracile sp. nov.. The available names Opilus congruus Newman, 1842 and Opilus femoralis Westwood, 1849, are respectively corrected to Opilo congruus Newman, 1842 and Opilo femoralis Westwood, 1849 in accordance with Article 11.9.3.2 of the Code (ICZN 1999). Lectotypes are designated for Opilo abdominalis Schenkling, 1901, Opilo congruus Newman, 1842, Opilo femoralis Westwood, 1849, Opilo variipes Chevrolat, Opilo doddi Schenkling, 1906 and Opilo pascoei Gorham, 1876.